Developing Socialization Processes in Early Childhood Through Playing - Dhea Intan Puspita Sari (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
Playing and children are a unity that is commonly claimed in many places. Playing and children are like a whole for both traditional and modern games. Nowadays, children prefer modern technology-based games which can be played at home without meeting other friends. In fact, interacting with friends can have a positive impact on the socialization process of children. This socialization process will slowly emerge when children play with their friends and hence traditional games are the right choice for this process. At the same time, traditional games that are slowly displaced by technological developments will indirectly be preserved again if we start to play it again. The method used in this paper is literacy study. The purpose of this paper is to train the children's socialization process using traditional game, which is slowly being forgotten as a tool to increase children’s socialization process